Taohong siwu decoction attenuates AIM2 and NLRC4 inflammasomes by ameliorates deoxyribonucleic acid damage after ischemic stroke - Wang, Ni; Chu, Furui; Zhang, Lijuan; Fei, Changyi; Yu, Chao; Xue, Sujun; Wang, Yongzhong; Fang, Ling; Peng, Daiyin; Duan, Xianchun; Chen, Weidong (Frontiers in Pharmacology, 2022)
Taohong Siwu Decoction (THSWD) has been shown to have a therapeutic effect on ischemic strokes (IS). However, it is not known whether THSWD can improve DNA damage after stroke and reduce the inflammatory response caused by the damage, thus treating IS. Therefore, we constructed an ischemic stroke model (I/R) in rats and performed oxygen-glucose deprivation/reoxygenation (OGD/R) on BV2 cells. Then ELISA, immunofluorescence staining, immunohistochemistry staining and RT-qPCR were performed to detect the expressions of AIM2, NLRC4 and Caspase-1 inflammasomes and other inflammatory factors. Experimental stroke causes DNA damage, and we found that the aforementioned inflammasomes as well as inflammatory factors were significantly suppressed after treatment with THSWD by comparing the model group with the model administration group. In addition, we examined the expression of AIM2, NLRC4 and caspase-1 in BV2 cells of OGD/R and found that the expression of the aforementioned inflammasomes was significantly decreased in OGD/R by administration of THSWD-containing serum. Our data suggest that THSWD can improve DNA damage after stroke as well as the inflammatory response caused by the damage.